A review of photovoice applications in environment, sustainability, and conservation contexts: is the method maintaining its emancipatory intents?. Issue 3 (3rd March 2020) - Derr, Victoria; Simons, Jordin
Abstract: Photovoice, a Participatory Action Research method developed by Wang and Burris, has gained popularity as a pedagogical tool to engage youth with environmental, sustainability, and conservation issues. Influenced by Paulo Freire's critical pedagogy, feminist theory, and documentary photography, photovoice supports reflection about place, critical dialogue about community issues, and social change by reaching policymakers. Some scholars have modified the method and applied varying frameworks to increase relevance for diverse participants. However, adaptation also may lose the original tenets. Through a scoping review, this study examined methodological applications to science, conservation, and sustainability education and whether emerging approaches align with Wang and Burris' original goals. The scoping review identified and analyzed four applications of photovoice: i) place as pedagogy, ii) conservation and sustainability, iii) STEM teaching; and iv) decolonizing education. Current scholarship shows promise for photovoice in environmental education applications to support participatory, diverse, and equitable educational settings, but some projects would benefit from more explicit attention to the original emancipatory intents of the method.